Gestational diabetes mellitus: current screening problems - N. I. Volkova; S. O. Panenko (Сахарный диабет)
Gestational diabetes mellitus (GDM) is characterized as hyperglycemia, first detected during pregnancy, yet not meeting the criteria for “manifest” diabetes mellitus. GDM is one of the most common gestational complications. This pathology is associated with many adverse pregnancy outcomes, both on the part of the mother and the fetus. The problem of identifying GDM has acquired particular relevance and significance for the healthcare system at the moment due to the steady increase in the prevalence of such risk factors of GDM as obesity and late pregnancy. The history of screening and diagnosis of GDM has undergone a number of significant changes in a short time. Currently, different clinical guidelines offer different approaches to GDM screening, thus, a unified approach to identifying this pathology has not yet been formulated and adopted. The purpose of this review was to discover the current clinical guidelines for the detection of GDM at 24–28 weeks of pregnancy, including historical context of their origin and development, to describe these approaches, as well as to critically evaluate them with a discussion of the main advantages and disadvantages of each of them.